Insights on the behavior of Late Paleozoic aquatic crustaceans (Pygocephalomorpha?): compound trace fossils from Western Argentina - Melchor, Ricardo Nestor (2014)
We describe intergradations between the arthropod repichnial trace fossils Diplichnites gouldi (Gevers et al., 1971), Dendroidichnites Demathieu et al., 1992, and Monomorphichnus Crimes, 1970 with two distinct cubichnial traces, Gluckstadtella cooperi Savage, 1971 and Huilmuichnus santracruzensis new ichnogenus and ichnospecies. These compound ichnofossils are part of high ichnodiversity arthropod-dominated trace fossil associations from the Late Carboniferous Agua Escondida Formation of the San Rafael Basin (Argentina). The complex ichnotaxonomy of Diplichnites and the ichnospecies D. gouldi are discussed and some possible working solutions are proposed. The most likely producer of the compound trace fossils are the Pygocephalomorpha, a group of Late Paleozoic crustaceans that are recorded in nearby basins from Uruguay and Brazil. The compound trace fossils are used to infer a number of complex behaviors of pygocephalomorphs in a subaqueous setting, including caridoid (tail flip) or more primitive escape reactions, landing followed by resting and transient resting during normal walking. In addition, different gaits can be inferred from well-preserved D. gouldi, which can be correlated with contrasting trackway morphology.